2014
DOI: 10.1021/es502696t
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Costs of the Chesapeake Bay Total Maximum Daily Load

Abstract: This study estimates costs to agricultural producers of the Watershed Implementation Plans (WIPs) developed by states in the Chesapeake Bay Watershed to comply with the Chesapeake Bay total maximum daily load (TMDL) and potential cost savings that could be realized by a more efficient selection of agricultural Best Management Practices (BMPs) and spatial targeting of BMP implementation. The cost of implementing the WIPs between 2011 and 2025 is estimated to be about $3.6 billion (in 2010 dollars). The annual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 8 publications
0
42
0
Order By: Relevance
“…Crumpton and Stenback [59] found that the creation of small reservoirs targeted to headwater streams draining cropland could reduce N flux substantially when A w :A r is <200. This contrasts to the high costs and uncertainty associated with many voluntary nonpoint abatement efforts that rely on locations of opportunity-rather than strategic locations where improved practices will generate the greatest effects on downstream delivery of pollution [60].…”
Section: Strategic Vs Opportunistic Views Of N Tradeoff Damsmentioning
confidence: 93%
“…Crumpton and Stenback [59] found that the creation of small reservoirs targeted to headwater streams draining cropland could reduce N flux substantially when A w :A r is <200. This contrasts to the high costs and uncertainty associated with many voluntary nonpoint abatement efforts that rely on locations of opportunity-rather than strategic locations where improved practices will generate the greatest effects on downstream delivery of pollution [60].…”
Section: Strategic Vs Opportunistic Views Of N Tradeoff Damsmentioning
confidence: 93%
“…Water quality trading analysts regularly produce ex ante empirical studies that show regulated sources could significantly reduce regulatory compliance costs by purchasing agricultural nonpoint nutrient reduction credits (Faeth, ; Fang et al ., ; Ribaudo et al ., ; Hanson and McConnell, ; Mehan, ; Sasaki and Caplan, ; Jones et al ., ; Van Houtven et al ., ; Perez et al ., ; Wainger et al ., ; Kaufman et al ., ). Costs typically include the financial costs of capital and operation and the maintenance associated with pollutant control technologies and practices.…”
Section: Water Quality Trading In the United Statesmentioning
confidence: 97%
“…The inequalities imply each participating point source has multiple partners. This is because an individual unregulated point source tends to generate sizable emissions relative to an individual nonpoint source (although, in aggregate, nonpoint emissions may be greater; Kaufman et al ), implying that a point source's demand exceeds the effective supply from an individual nonpoint source. We write the number of partners more generally as Y z ( x , τ ), where x is the vector of demand and supply variables, and τ = [ τ Aw , w τ Ag , g τ Ag , w ] is the vector of trade ratios.…”
Section: The Permit Marketmentioning
confidence: 99%